Agonistic β2-Adrenergic Receptor Autoantibodies Characterize the Aqueous Humor of Patients With Primary and Secondary Open-Angle Glaucoma - Hohberger, Bettina; Wörn, Max; Lämmer, Robert; Mahajan, Aparna; Mardin, Christian; Schötzer-Schrehardt, Ursula; Kunze, Rudolph; Herrmann, Martin; Wallukat, Gerd (Frontiers in Immunology, 2021)
Purpose: Agonistic β2-adrenergic receptor autoantibodies (β2-agAAb) were recently observed in sera of patients with ocular hypertension (OHT), primary (POAG) and secondary open-angle glaucoma (SOAG), yet not in healthy controls (HC).(Hohberger et al., 2019a) It was the aim of the present study to investigate the presence of β2-agAAb in aqueous humor (AH) samples of OAG patients and to correlate these with the corresponding β2-agAAb serum data. Material and Methods: Thirty-nine patients (21 male, 18 female) were recruited from the Department of Ophthalmology, University of Erlangen-Nürnberg: twenty-one POAG, 18 SOAG. Aqueous humor samples were collected during minimal invasive glaucoma surgery. Serum and AH samples were analyzed for β2-agAAb by a bioassay quantifying the beating rate of cultured cardiomyocyte (cut-off: 2 U). Results: Thirty-six of 39 (92.3%) and 34 of 39 (87.2%) of OAG patients showed a β2-agAAb in their sera and AH samples, respectively. All β2-agAAb AH-positive OAG patients were also seropositive. We also observed a β2-agAAb seropositivity in 95% and 89% of patients with POAG and SOAG, respectively. Beta2-agAAb were seen in 86% (POAG) and 78% (SOAG) of AH samples. The β2-agAAb adrenergic activity were increased in the AH of patients with POAG (6.5 ± 1.5 U) when compared with those with SOAG (4.1 ± 1.1 U; p = 0.004). Serum β2-agAAb adrenergic activity did not differ between the cohorts (POAG (4.5 ± 1.5 U); SOAG (4.6 ± 2.1 U; p=0.458)). No correlation of the beating rates were observed between serum and AH samples for group and subgroup analyses. Conclusion: The detection of β2-agAAb in systemic and local circulations supports the hypothesis of a direct functional impact of these agAAb on ocular G-protein coupled receptors. The high prevalence of β2-agAAb in serum and AH samples of patients with POAG or SOAG suggests a common role of these AAb in the etiopathogenesis of glaucoma, independent of open-angle glaucoma subtype.